1999
DOI: 10.1046/j.1365-294x.1999.00745.x
|View full text |Cite
|
Sign up to set email alerts
|

Phylogeographical population structure of tiger quolls Dasyurus maculatus (Dasyuridae: Marsupialia), an endangered carnivorous marsupial

Abstract: Tiger quolls, Dasyurus maculatus, are the largest carnivorous marsupials still extant on the mainland of Australia, and occupy an important ecological niche as top predators and scavengers. Two allopatric subspecies are recognized, D.m. gracilis in north Queensland, and D.m. maculatus in the southeast of the mainland and Tasmania. D.m. gracilis is considered endangered while D.m. maculatus is listed as vulnerable to extinction; both subspecies are still in decline. Phylogeographical subdivision was examined to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(40 citation statements)
references
References 53 publications
1
39
0
Order By: Relevance
“…In fact, the minimum sequence divergence between the taxa was only 0.47% (three substitutions; Figure 2). This value is substantially less than the minimum differences observed between P. xanthopus subspecies (5.20%; Pope et al, 1996), and between mainland and Tasmanian tiger quolls, Dasyurus maculatus (2.71%; Firestone et al, 1999).…”
Section: Genetic Diversitymentioning
confidence: 65%
“…In fact, the minimum sequence divergence between the taxa was only 0.47% (three substitutions; Figure 2). This value is substantially less than the minimum differences observed between P. xanthopus subspecies (5.20%; Pope et al, 1996), and between mainland and Tasmanian tiger quolls, Dasyurus maculatus (2.71%; Firestone et al, 1999).…”
Section: Genetic Diversitymentioning
confidence: 65%
“…Regardless, Belcher and Darrant (2004) concluded that adult females tolerated the presence of juvenile and subadult female offspring, a system referred to as female natal philopatry. Genetic evidence so far gathered on spatial relationships of individuals within populations of the species also suggests this form of population arrangement (Firestone et al 1999). Tissue samples collected from each of our study animals are currently being genetically assessed and should provide some information about relationships between individuals in the local population, particularly with regard to mother-daughter lineages.…”
Section: Home-range Size and Spatial Organisationmentioning
confidence: 83%
“…Fossil evidence for a Nothofagus tree species on King Island 38 kya suggests that moist forest vegetation occurred along the Bass Strait land bridges [82], enabling dispersal of the delicate skink into TAS. Although some other species appear not to have used these recent land bridges (frog: Crinia signigera , [79]; reptiles: Acritoscincus duperreyi , [76]; Lerista bougainvilli , [83]; mammals: Dasyurus maculatus , [84]), others appear to have dispersed across these Bass Strait land bridges (frogs: Limnodynastes peronii and tasmaniensis , [67]; reptiles: Liopholis whitii , [73]; Notechis scutatus , [85]) (Table 2). The repeated presence of the land bridges has also restricted east-west gene flow across Bass Strait in several marine invertebrate species ([86-89]; Table 2).…”
Section: Discussionmentioning
confidence: 99%